Sports Cardiology - Al Najem S; 2; Groll A; Schmermund A; 5; Nowak B; 5; Voigtländer T; 5; Kaltenbach U; Dohmann P; Andresen D 6; et al. (Deutsche Zeitschrift für Sportmedizin)
Background: Keeping patients active is an essential goal of cardiac rehabilitation (CR). This research aims to analyze the development of steps/day after CR.Methods: 126 adult, stable cardiac patients who had completed treatment for their acute condition, usually acute coronary syndrome or heart failure, were enrolled during CR and advised for daily step recording up to one year post CR. Mean number of steps during and for 3 weeks post CR were compared by paired t-test. Furthermore, influence of gender, age, smoking, NYHA, EF, BMI, day of the year, and length of time post CR on steps/day were estimated using a generalized additive regression model.Results: Compared to CR, steps/day increased on average by 925steps/day in the first 3 weeks (p<0.001). Time post CR did not significantly affect walking activity (+0.35 steps/day, p>0.05), whereas seasonal correlations existed, indicating a summer increase and a winter decline (p<0.001). Mean steps/day during one-year post CR were reduced in female (-402 steps/day, p<0.001), older (-51steps/year, p<0.001), overweight/obese patients (non-linear, p<0.001), in smokers (-725 steps/day, p<0.001) and ex-smokers (-1,119 steps/day, p<0.001), in patients with higher NYHA class (NYHA2:-1,216 steps/day, NYHA3:-1,946 steps/day, p<0.001) and EF group (EF2-4:-711 steps/day, p<0.001).Conclusion: Walking activity remains high during one-year post CR. Therefore, CR appears to exert a sizeable effect but needs to be pursued and individualized for further optimization. KEY WORDS: Pedometer, Physical Activity, Step Recommendation, Coronary Heart Disease, Heart Failure